Sistem Pakar Penyakit Menular Menggunakan Dempster Shafer Dengan Rekomendasi Tempat Layanan Kesehatan - Istiadi Istiadi; Emma Budi Sulistiarini; Rudy Joegijantoro; Dedi Usman Effendy (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Delay in the handling of a type of disease can pose a risk for someone who has the surrounding environment. Often the casualties are caused by people's ignorance of the spread of dangerous infectious diseases. People's ignorance as an action that must be done immediately and where to do to get help. Thus it is necessary to build an application of an expert system that can diagnose infectious diseases, provide recommendations for disease management, and provide recommendations for appropriate and acceptable health services. The system was built to diagnose six types of infectious diseases that are of particular concern to Malang City. Various infectious diseases with similar symptoms that appear will lead to the possibility of a diagnosis and many possibilities for diagnosis. The Dempster Shafer method is an approved one that can be used in overcoming these factors. The disease expert consultation system application using the Dempster Shafer method obtained an accuracy test result of 88.5%. While the system usability test obtained results, 76% agreed to system reliability, 85% strongly agreed to system efficiency, 83% strongly agreed to ease for use system, and 79% agreed to accurate system.